2018
DOI: 10.1128/mbio.00716-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host Factors Involved in Human Cytomegalovirus Replication, Assembly, and Egress Using a Two-Step Small Interfering RNA Screen

Abstract: As obligate intracellular parasites, viruses are completely dependent on host factors for replication. Assembly and egress of complex virus particles, such as human cytomegalovirus (HCMV), are likely to require many host factors. Despite this, relatively few have been identified and characterized. This study describes a novel high-throughput, two-step small interfering RNA (siRNA) screen, which independently measures virus replication and virus production. By combining data from replication and virus productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…GFP fluorescence levels were monitored every 24 hours for seven days, with levels compared to control non-targeting siRNA transfected cells in order to determine the effect of individual gene depletion on HCMV replication. We have previously established GFP expression as an accurate measure of early virus replication events including viral entry, translocation to the nucleus and viral DNA amplification, hereon referred to as primary replication (12, 13). The assay was performed in biological triplicate with an additional replicate used to determine cytotoxicity at seven days post-infection (DPI) (supplemental table 1).…”
Section: Resultsmentioning
confidence: 99%
“…GFP fluorescence levels were monitored every 24 hours for seven days, with levels compared to control non-targeting siRNA transfected cells in order to determine the effect of individual gene depletion on HCMV replication. We have previously established GFP expression as an accurate measure of early virus replication events including viral entry, translocation to the nucleus and viral DNA amplification, hereon referred to as primary replication (12, 13). The assay was performed in biological triplicate with an additional replicate used to determine cytotoxicity at seven days post-infection (DPI) (supplemental table 1).…”
Section: Resultsmentioning
confidence: 99%
“…While this approach allows for rapid, efficient and real-time measurement of signal, any effects on virus replication are biased toward early events such as entry and genome replication and may be less effective at measuring late events such as assembly and egress. Previously we showed that measuring viral replication based on expression of fluorescence cassette incorporated into the virus genome alone, was a poor predictor of effects on late aspects of virus replication (McCormick et al, 2018). Furthermore, basing the readout directly on a fluorescent reporter can result in the identification of genes that have a direct effect on the fluorescent signal rather than through inhibition or promotion of virus replication.…”
Section: Systematic Identification Of Novel Host-virus Interactions Umentioning
confidence: 99%
“…RNA sequencing and mass spectrometry allow the temporal and spatial expression of viral and host factors to be monitored during the course of infection, subsequently discovering the mechanism of viral manipulation of host machinery and the host factors important for virus replication (Weekes et al, 2014;Jean Beltran et al, 2016). In addition, the expression of host genes can be systematically silenced through the RNA-induced silencing complex (RISC) or disrupted via clustered regularly interspaced short palindromic repeats (CRISPR) technology (Polachek et al, 2016;McCormick et al, 2018). The resulting effects of individual gene depletion or disruption on virus replication can be examined using a reporter system such as luminescence, enhanced green fluorescence protein (eGFP), or immunofluorescence staining for viral proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Such a focused library targeting genes involved in membrane trafficking was used to identify host factors that influence assembly and egress of human cytomegalovirus [ 39 ]. In this small screen of 140 targets, identification of host factors involved in late steps of the virus cycle was possible thanks to a two-step readout strategy based on both the fluorescent reporter expression and the amount of progeny virus produced.…”
Section: Assay Design and Screening Formatmentioning
confidence: 99%
“…However, multiple chromosomal aberrations, aneuploidy, and variable chromosome content are widely observed in these cell lines [ 38 ]. Moreover, many cell lines bear defects in innate immunity signaling pathways, while the study of innate immunity requires that full or at least partial functionality of this system [ 39 ]. An excellent example of this is the cGAS/STING-sensing pathway, which is commonly suppressed in cancers to escape DNA damage responses and sustain genomic instability.…”
Section: Introductionmentioning
confidence: 99%